Porous anti-drag coating and preparation method thereof
By preparing a porous drag-reducing coating with a vertical pore structure and a porous crosslinked coating on the surface of the navigation body in water, the problems of easy wear and flexible surface deformation of the drag-reducing surface in the prior art are solved, and efficient drag-reducing performance is achieved.
Patent Information
- Application Number
- CN202411640085.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-18
- Publication Date
- 2025-04-04
- Estimated Expiration
- 2044-11-18
AI Technical Summary
In the prior art, the superhydrophobic drag-reducing surface is prone to wear and has poor resistance stability. The flexible drag-reducing surface will permanently deform when the external flow field is too strong, losing the drag-reducing effect. There is no good solution yet.
By coating a mixture of natural polymers, cellulose nanocrystals, two-dimensional nanomaterials and water on a substrate and immersing them in a metal salt solution to form a metal ion coordination crosslinked coating, a crosslinked coating with a vertical pore structure is made using directional frozen casting technology, and then a porous crosslinked coating is constructed through inorganic salt templates and hot pressing technology.
The preparation of a porous drag-reducing coating has been achieved, with the characteristics of combining rigidity and flexibility and rough surface, good mechanical stability, obvious micro-eddy current, and excellent drag-reducing performance.
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of marine drag reduction materials, and in particular relates to a porous drag reduction coating and a preparation method thereof. Background Art
[0002] Ships, underwater vessels and other underwater navigation bodies are affected by friction resistance during underwater movement, which reduces their speed and significantly increases energy consumption. At present, superhydrophobic drag reduction and flexible drag reduction are the more common drag reduction technologies in the field. Superhydrophobic drag reduction usually requires the construction of a rigid surface with a rough structure and very low interaction force with water, but the rigid rough superhydrophobic surface is easy to wear and has poor drag reduction stability. Flexible drag reduction technology represented by dolphin skin does not have as strict restrictions on the flow field as rigid superhydrophobic surfaces, but once the external flow field is too strong, the flexible surface will be permanently deformed and cannot be restored, thereby losing the drag reduction effect. Based on the problems in the existing technology, there is no better solution. Summary of the invention
[0003] The purpose of the present invention is to provide a porous drag-reducing coating with a rough structure and both rigidity and flexibility and a preparation method thereof in view of the above-mentioned problems existing in the prior art.
[0004] To achieve the above objectives, the technical solution of the present invention is as follows: In a first aspect, the present invention provides a method for preparing a porous drag reducing coating, the preparation method comprising: A mixture of natural polymers, cellulose nanocrystals, two-dimensional nanomaterials and water is coated on a substrate, and then taken out after being immersed in a metal salt solution for a certain period of time to obtain a cross-linked coating coordinated by metal ions; The cross-linked coating with vertical pore structure is obtained by treating the metal ion coordinated cross-linked coating with directional freeze casting technology. The cross-linked coating having a vertical pore structure is immersed in an organic-inorganic mixed solution for a certain period of time, then taken out, and the inorganic salt therein is removed to obtain a porous cross-linked coating; the organic-inorganic mixed solution is obtained by mixing a silane coupling agent, an inorganic precursor, an inorganic salt, an adhesive polymer, and an organic solvent; The porous cross-linked coating is hot pressed to obtain a porous drag-reducing coating.
[0005] The natural polymer is at least one of agar, sodium alginate and chitosan; The cellulose nanocrystal is at least one of sulfonated cellulose nanocrystal, aminated cellulose nanocrystal, carboxylated cellulose nanocrystal, and phosphorylated cellulose nanocrystal; The two-dimensional nanomaterial is at least one of graphene oxide, molybdenum disulfide, and boron nitride; The metal salt is at least one of calcium chloride, ferric chloride, cerium nitrate and neodymium chloride.
[0006] The mass fractions of natural polymer, cellulose nanocrystal and two-dimensional nanomaterial in the mixed solution are 0.5-10wt%, 0.1-10wt% and 0.01-5wt% respectively; The mass fraction of the metal salt in the metal salt solution is 0.01-10wt%; The silane coupling agent is at least one of vinyl triethoxysilane, methacryloxypropyl trimethoxysilane and γ-mercaptopropyl triethoxysilane; The inorganic precursor is at least one of tetraethyl orthosilicate and tetrabutyl titanate; The inorganic salt is at least one of sodium chloride, magnesium chloride and sodium sulfate; The adhesive polymer is at least one of polyurethane, amino silicone resin, and fluorocarbon resin; The organic solvent is at least one of methanol and ethanol.
[0007] The mass fractions of the silane coupling agent, the inorganic precursor and the inorganic salt adhesive polymer in the organic-inorganic mixed liquid are 5-10wt%, 0.5-15wt%, 0.5-10wt% and 0.5-5wt% respectively.
[0008] The hot pressing temperature is 60-120° C., and the hot pressing time is 0.5-24 hours.
[0009] The treatment of the metal ion coordinated cross-linked coating by directional freeze casting technology refers to: freezing for 0.5-24 hours in a -60°C to -4°C environment, and then freeze drying for 6-72 hours.
[0010] The organic-inorganic mixed solution also includes an additive with a mass fraction of 0.5-10wt%, and the additive is at least one of montmorillonite, diatomaceous earth and halloysite.
[0011] The reaction temperature for obtaining the organic-inorganic mixed solution is 5-65°C.
[0012] In a second aspect, the present invention provides a porous drag-reducing coating, wherein the porous drag-reducing coating is prepared by the aforementioned preparation method.
[0013] Compared with the prior art, the present invention has the following beneficial effects: The present invention provides a method for preparing a porous drag-reducing coating. First, a cross-linked coating with a vertical pore structure is manufactured by metal ion coordination and directional freeze casting technology. On this basis, a porous cross-linked coating with a surface porous structure is further constructed by in-situ filling of inorganic materials and inorganic salt template technology, so that the finally obtained porous drag-reducing coating has the characteristics of both rigidity and flexibility and surface roughness, good mechanical stability, obvious micro-eddies, and excellent drag reduction performance. DETAILED DESCRIPTION
[0014] The present invention is further described in detail below in conjunction with specific implementation methods and solutions.
[0015] A method for preparing a porous drag-reducing coating, the method comprising: A mixture of natural polymers, cellulose nanocrystals, two-dimensional nanomaterials and water is coated on a substrate, and then taken out after being immersed in a metal salt solution for a certain period of time to obtain a cross-linked coating coordinated by metal ions; The cross-linked coating with vertical pore structure is obtained by treating the metal ion coordinated cross-linked coating with directional freeze casting technology. The cross-linked coating having a vertical pore structure is immersed in an organic-inorganic mixed solution for a certain period of time, then taken out, and the inorganic salt therein is removed to obtain a porous cross-linked coating; the organic-inorganic mixed solution is obtained by mixing a silane coupling agent, an inorganic precursor, an inorganic salt, an adhesive polymer, and an organic solvent; The porous cross-linked coating is hot pressed to obtain a porous drag-reducing coating.
[0016] Optionally, the natural polymer is at least one of agar, sodium alginate and chitosan; The cellulose nanocrystal is at least one of sulfonated cellulose nanocrystal, aminated cellulose nanocrystal, carboxylated cellulose nanocrystal, and phosphorylated cellulose nanocrystal; Optionally, the two-dimensional nanomaterial is at least one of graphene oxide, molybdenum disulfide, and boron nitride; The metal salt is at least one of calcium chloride, ferric chloride, cerium nitrate and neodymium chloride.
[0017] Optionally, the mass fractions of natural polymer, cellulose nanocrystal and two-dimensional nanomaterial in the mixed solution are 0.5-10wt%, 0.1-10wt% and 0.01-5wt% respectively; The mass fraction of the metal salt in the metal salt solution is 0.01-10wt%; Optionally, the silane coupling agent is at least one of vinyl triethoxysilane, methacryloxypropyl trimethoxysilane, and γ-mercaptopropyl triethoxysilane; The inorganic precursor is at least one of tetraethyl orthosilicate and tetrabutyl titanate; The inorganic salt is at least one of sodium chloride, magnesium chloride and sodium sulfate; The adhesive polymer is at least one of polyurethane, amino silicone resin, and fluorocarbon resin; The organic solvent is at least one of methanol and ethanol.
[0018] Optionally, the mass fractions of the silane coupling agent, the inorganic precursor, and the inorganic salt adhesive polymer in the organic-inorganic mixed liquid are 5-10wt%, 0.5-15wt%, 0.5-10wt%, and 0.5-5wt%, respectively.
[0019] Optionally, the hot pressing temperature is 60-120° C., and the hot pressing time is 0.5-24 h.
[0020] Optionally, the treatment of the metal ion coordinated cross-linked coating using directional freeze casting technology refers to: freezing at -60°C to -4°C for 0.5-24h, and then freeze-drying for 6-72h.
[0021] Optionally, the organic-inorganic mixed solution further comprises an additive with a mass fraction of 0.5-10 wt %, and the additive is at least one of montmorillonite, diatomaceous earth and halloysite.
[0022] Optionally, the reaction temperature for obtaining the organic-inorganic mixed solution is 5-65°C.
[0023] A porous drag-reducing coating is prepared by the aforementioned preparation method.
[0024] The principle of the present invention is described as follows: First, a mixture of natural polymers, cellulose nanocrystals, two-dimensional nanomaterials and water is coated on a substrate, immersed in a metal salt solution for a certain period of time and then taken out. The metal ions in the metal salt solution form coordination with the abundant hydroxyl groups in the cellulose nanocrystals, and a cross-linked coating is formed by introducing metal coordination cross-linking. The metal ion coordinated cross-linked coating is then treated with directional freeze casting technology to produce a cross-linked coating with a vertical pore structure and a vertical orientation structure; the principle of directional freeze casting technology is: the metal ion coordinated cross-linked coating is placed in a temperature field to cool down, and the water will gradually solidify along the temperature gradient. The ice crystal columns generated by solidification squeeze, push away, and embed the skeleton of the metal ion coordinated cross-linked coating between the ice crystal columns; placed in a freeze dryer for drying, as the pressure is gradually reduced at room temperature, the ice crystal columns begin to change from solid phase to liquid phase to gas phase, and after the ice crystal column template is removed, a vertical pore structure is formed at the original position of the ice crystal column, and the metal ion coordinated cross-linked coating skeleton arranged by the ice crystal column is retained, and finally a cross-linked coating with a vertical orientation structure of a two-dimensional nanosheet is obtained to improve the structural stability of the cross-linked coating.
[0025] The cross-linked coating with vertical pore structure is immersed in an organic-inorganic mixed liquid. Since the organic-inorganic mixed liquid is obtained by mixing silane coupling agent, inorganic precursor, inorganic salt, adhesive polymer and organic solvent, the silane coupling agent and the inorganic precursor undergo hydrolysis and condensation reaction to generate inorganic materials; the hydrolysis and condensation reaction will occur in the vertical pore structure of the cross-linked coating, realizing the in-situ filling of the inorganic material, and at the same time, the adhesive polymer enters the gap between the inorganic particles and the vertical pore structure, playing a "rivet" role, improving the interfacial compatibility between the inorganic material and the cross-linked coating. There are many active groups on the inorganic material, which can form hydrogen bonds with the inorganic salt. After removing the inorganic salt, a pore structure is formed at the original location of the inorganic salt, and a porous cross-linked coating is obtained. Finally, the final porous drag reduction coating is obtained by hot pressing technology. When in use, the water flow generates micro-eddies in the downstream direction in the pore structure on the surface of the porous drag reduction coating, causing the boundary layer to slip, thereby significantly reducing the friction resistance.
[0026] Embodiment 1: A method for preparing a porous drag-reducing coating is carried out in the following steps: Step 1: first add natural polymer, cellulose nanocrystal and two-dimensional nanomaterial into deionized water, stir at 5°C for 24h to obtain a mixed solution; evenly coat the mixed solution on a substrate (coating thickness is 100µm), let stand at room temperature for 1min, and then immerse in a metal salt solution at 5°C for 0.1h to obtain a cross-linked coating coordinated by metal ions; the mass fractions of natural polymer, cellulose nanocrystal and two-dimensional nanomaterial in the mixed solution are 0.5wt%, 10wt% and 5wt%, respectively; the natural polymer is agar; the cellulose nanocrystal is sulfonated cellulose nanocrystal; the two-dimensional nanomaterial is graphene oxide nanosheet; the mass fraction of metal salt in the metal salt solution is 10wt%; the metal salt is calcium chloride; Step 2: Take out the metal ion coordinated cross-linked coating prepared in step 1, wash it with deionized water, and then process it using directional ice crystal freeze casting technology to construct a cross-linked coating with a vertical pore structure; the directional ice crystal freeze casting can be: first place the sample in a freezing chamber of a freeze casting machine for unidirectional freezing, gradually cool it to -60°C, and the freezing time of the entire unidirectional freezing process is 0.5h; then place it in a freeze dryer for freeze drying for 6h; Step 3, mixing a silane coupling agent, an inorganic precursor, an inorganic salt (particle size of 0.1µm), an additive (particle size of 0.1µm), an adhesive polymer, and an organic solvent, and stirring at 5°C for 0.5h to obtain an organic-inorganic mixed solution; the mass fractions of the silane coupling agent, inorganic precursor, inorganic salt, additive, and adhesive polymer in the organic-inorganic mixed solution are 0.5wt%, 0.5wt%, 0.5wt%, 0.5wt%, 0.5wt%, and 0.5wt%, respectively; the silane coupling agent is vinyl triethoxysilane; the inorganic precursor is tetraethyl orthosilicate; the inorganic salt is sodium chloride; the additive is montmorillonite; the adhesive polymer is polyurethane; and the organic solvent is methanol; Step 4: Take out the metal ion coordinated cross-linked coating prepared in step 2, thaw it at room temperature, and then immerse it in the organic-inorganic mixed solution prepared in step 3 for 0.5 h to obtain a cross-linked coating filled with inorganic materials in situ; Step 5: Take out the cross-linked coating filled with inorganic materials in situ prepared in step 4, immerse it in deionized water for 1 hour to remove the inorganic salt template, and obtain a porous cross-linked coating with a porous structure on the surface; Step 6: Hot-press the porous cross-linked coating prepared in step 5 at 60° C. for 24 hours to finally obtain a porous drag-reducing coating.
[0027] After water tunnel testing, the coating's drag reduction rate was 9.7%.
[0028] Embodiment 2: A method for preparing a porous drag-reducing coating is carried out in the following steps: Step 1: Add natural polymer, cellulose nanocrystal and two-dimensional nanomaterial into deionized water, stir at 95℃ for 0.5h to obtain a mixed solution; evenly coat the mixed solution on the substrate (coating thickness is 2cm), let it stand at room temperature for 10min, and then immerse it in a metal salt solution at 95℃ for 24h to obtain a cross-linked coating coordinated by metal ions; the mass fractions of natural polymer, cellulose nanocrystal and two-dimensional nanomaterial in the mixed solution are 10wt%, 0.1wt% and 0.01wt%, respectively; the natural polymer is sodium alginate; the cellulose nanocrystal is amino cellulose nanocrystal; the two-dimensional nanomaterial is molybdenum disulfide nanosheet; the mass fraction of metal salt in the metal salt solution is 0.01wt%; the metal salt is ferric chloride; Step 2: Take out the metal ion coordinated cross-linked coating prepared in step 1, wash it with deionized water, and then process it using directional ice crystal freeze casting technology to construct a cross-linked coating with a vertical pore structure; the directional ice crystal freeze casting can be: first place the sample in a freezing chamber of a freeze casting machine for unidirectional freezing, gradually cool it to -60°C, and the freezing time of the entire unidirectional freezing process is 10 hours; then place it in a freeze dryer for freeze drying for 20 hours; Step 3: Mix a silane coupling agent, an inorganic precursor, an inorganic salt (particle size of 100µm), an additive (particle size of 50µm), an adhesive polymer, and an organic solvent, and stir at 65°C for 24h to obtain an organic-inorganic mixed solution; the mass fractions of the silane coupling agent, inorganic precursor, inorganic salt, additive, and adhesive polymer in the organic-inorganic mixed solution are 10wt%, 15wt%, 10wt%, 10wt%, and 5wt%, respectively; the silane coupling agent is methacryloxypropyltrimethoxysilane; the inorganic precursor is tetrabutyl titanate; the inorganic salt is magnesium chloride; the additive is diatomaceous earth; the adhesive polymer is amino silicone resin; and the organic solvent is ethanol; Step 4: Take out the metal ion coordinated cross-linked coating prepared in step 2, thaw it at room temperature, and then immerse it in the organic-inorganic mixed solution prepared in step 3 for 24 hours to obtain a cross-linked coating filled with inorganic materials in situ; Step 5: Take out the cross-linked coating filled with inorganic materials in situ prepared in step 4, immerse it in deionized water for 56 hours to remove the inorganic salt template, and obtain a porous cross-linked coating with a porous structure on the surface; Step 6: hot-press the porous cross-linked coating prepared in step 5 at 120° C. for 0.5 h to finally obtain a porous drag-reducing coating.
[0029] After water tunnel testing, the coating's drag reduction rate was 8.9%.
[0030] Embodiment 3: A method for preparing a porous drag-reducing coating is carried out in the following steps: Step 1: Add natural polymer, cellulose nanocrystal and two-dimensional nanomaterial into deionized water, stir at 65℃ for 14h to obtain a mixed solution; evenly coat the mixed solution (coating thickness is 1000µm) on the substrate, let it stand at room temperature for 5min, and then immerse it in a metal salt solution at 75℃ for 10h to obtain a cross-linked coating coordinated by metal ions; the mass fractions of natural polymer, cellulose nanocrystal and two-dimensional nanomaterial in the mixed solution are 3wt%, 4wt% and 1wt%, respectively; the natural polymer is chitosan; the cellulose nanocrystal is carboxylated cellulose nanocrystal; the two-dimensional nanomaterial is boron nitride nanosheet; the mass fraction of metal salt in the metal salt solution is 2wt%; the metal salt is neodymium chloride; Step 2: Take out the metal ion coordinated cross-linked coating prepared in step 1, wash it with deionized water, and then process it using directional ice crystal freeze casting technology to construct a cross-linked coating with a vertical pore structure; the directional ice crystal freeze casting can be: first place the sample in a freezing chamber of a freeze casting machine for unidirectional freezing, gradually cool it to -30°C, and the freezing time of the entire unidirectional freezing process is 24 hours; then place it in a freeze dryer for freeze drying for 72 hours; Step 3: Mix a silane coupling agent, an inorganic precursor, an inorganic salt (particle size of 50 µm), an additive (particle size of 20 µm), an adhesive polymer, and an organic solvent, and stir at 45 ° C for 12 hours to obtain an organic-inorganic mixed solution; the mass fractions of the silane coupling agent, inorganic precursor, inorganic salt, additive, and adhesive polymer in the organic-inorganic mixed solution are 3wt%, 3wt%, 5wt%, 6wt%, and 3wt%, respectively; the silane coupling agent is γ-mercaptopropyltriethoxysilane; the inorganic precursor is tetraethyl orthosilicate; the inorganic salt is sodium sulfate; the additive is halloysite; the adhesive polymer is fluorocarbon resin; and the organic solvent is ethanol; Step 4: Take out the metal ion coordinated cross-linked coating prepared in step 2, thaw it at room temperature, and then immerse it in the organic-inorganic mixed solution prepared in step 3 for 8 hours to obtain a cross-linked coating filled with inorganic materials in situ; Step 5: Take out the cross-linked coating filled with inorganic materials in situ prepared in step 4, immerse it in deionized water for 36 hours to remove the inorganic salt template, and obtain a porous cross-linked coating with a porous structure on the surface; Step 6: Hot-press the porous cross-linked coating prepared in step 5 at 80° C. for 12 hours to finally obtain a porous drag-reducing coating.
[0031] After water tunnel testing, the coating's drag reduction rate was 10.5%.
[0032] Embodiment 4: A method for preparing a porous drag-reducing coating is carried out in the following steps: Step 1: Add natural polymer, cellulose nanocrystal and two-dimensional nanomaterial into deionized water, stir at 45°C for 8h to obtain a mixed solution; evenly coat the mixed solution (coating thickness is 1500µm) on the substrate, let it stand at room temperature for 8min, and then immerse it in a metal salt solution at a temperature of 55°C for 15h to obtain a cross-linked coating coordinated by metal ions; the mass fractions of natural polymer, cellulose nanocrystal and two-dimensional nanomaterial in the mixed solution are 5wt%, 5wt% and 3.5wt% respectively; the natural polymer is agar; the cellulose nanocrystal is phosphorylated cellulose nanocrystal; the two-dimensional nanomaterial is boron nitride nanosheet; the mass fraction of metal salt in the metal salt solution is 5wt%; the metal salt is neodymium chloride; Step 2: Take out the metal ion coordinated cross-linked coating prepared in step 1, wash it with deionized water, and then process it using directional ice crystal freeze casting technology to construct a cross-linked coating with a vertical pore structure; the directional ice crystal freeze casting can be: first place the sample in a freezing chamber of a freeze casting machine for unidirectional freezing, gradually cool it to -50°C, and the freezing time of the entire unidirectional freezing process is 12 hours; then place it in a freeze dryer for freeze drying for 60 hours; Step 3, mixing a silane coupling agent, an inorganic precursor, an inorganic salt (particle size of 50µm), an additive (particle size of 20µm), an adhesive polymer, and an organic solvent, and stirring at 65°C for 24h to obtain an organic-inorganic mixed solution; the mass fractions of the silane coupling agent, inorganic precursor, inorganic salt, additive, and adhesive polymer in the organic-inorganic mixed solution are 5wt%, 5wt%, 10wt%, 5wt%, and 5wt%, respectively; the silane coupling agent is vinyl triethoxysilane; the inorganic precursor is tetraethyl orthosilicate; the inorganic salt is sodium sulfate; the additive is halloysite; the adhesive polymer is fluorocarbon resin; and the organic solvent is ethanol; Step 4: Take out the metal ion coordinated cross-linked coating prepared in step 2, thaw it at room temperature, and then immerse it in the organic-inorganic mixed solution prepared in step 3 for 10 hours to obtain a cross-linked coating filled with inorganic materials in situ; Step 5: Take out the cross-linked coating filled with inorganic materials in situ prepared in step 4, immerse it in deionized water for 48 hours to remove the inorganic salt template, and obtain a porous cross-linked coating with a porous structure on the surface; Step 6: Hot-press the porous cross-linked coating prepared in step 5 at 90° C. for 10 hours to finally obtain a porous drag-reducing coating.
[0033] After water tunnel testing, the coating's drag reduction rate was 12.4%.
[0034] Comparative Example 1: This comparative example is substantially the same as Example 4, except that: In step 1, the concentration of the metal salt solution is 0wt%, and the coordination effect of metal ions is lacking, so a cross-linked coating cannot be obtained and the drag reduction performance test cannot be performed.
[0035] Comparative Example 2: This comparative example is substantially the same as Example 4, except that: Without the ice crystal freeze casting technology in step 2, it is impossible to obtain a vertical pore structure and to achieve the in-situ filling of inorganic materials in step 4. The resulting coating has poor strength and is brittle, and it is impossible to perform drag reduction performance tests.
[0036] Comparative Example 3: This comparative example is substantially the same as Example 4, except that: Without step 3 and step 4, it is impossible to achieve the in-situ filling of inorganic materials in step 4. The final coating has poor strength and is brittle, and it is impossible to perform drag reduction performance testing.
[0037] Comparative Example 4: This comparative example is substantially the same as Example 4, except that: The inorganic salt template dissolution in step 5 is missing. The final coating surface is dense, without porous structure and micro-eddy effect. After water tunnel testing, the coating drag reduction rate is 0.4%.
[0038] Comparative Example 5: This comparative example is substantially the same as Example 4, except that: The hot pressing process in step 6 is missing. The resulting coating has a large interlayer spacing and a loose structure. There is material shedding during the water tunnel drag reduction test.
[0039] By comparing Example 4 with Comparative Examples 1-5, it can be seen that the porous drag reduction coating prepared by the present invention has the characteristics of both rigidity and flexibility and surface roughness, good mechanical stability, obvious micro-eddies, and excellent drag reduction performance.
Claims
1. A method for preparing a porous drag-reducing coating, characterized in that: The preparation method comprises: A mixture of natural polymers, cellulose nanocrystals, two-dimensional nanomaterials and water is coated on a substrate, and then taken out after being immersed in a metal salt solution for a certain period of time to obtain a cross-linked coating coordinated by metal ions; The cross-linked coating with vertical pore structure is obtained by treating the metal ion coordinated cross-linked coating with directional freeze casting technology. The cross-linked coating having a vertical pore structure is immersed in an organic-inorganic mixed solution for a certain period of time, then taken out, and the inorganic salt therein is removed to obtain a porous cross-linked coating; the organic-inorganic mixed solution is obtained by mixing a silane coupling agent, an inorganic precursor, an inorganic salt, an adhesive polymer, and an organic solvent; The porous cross-linked coating is hot pressed to obtain a porous drag-reducing coating.
2. The method for preparing a porous drag-reducing coating according to claim 1, characterized in that: The natural polymer is at least one of agar, sodium alginate and chitosan; The cellulose nanocrystal is at least one of sulfonated cellulose nanocrystal, aminated cellulose nanocrystal, carboxylated cellulose nanocrystal, and phosphorylated cellulose nanocrystal; The two-dimensional nanomaterial is at least one of graphene oxide, molybdenum disulfide, and boron nitride; The metal salt is at least one of calcium chloride, ferric chloride, cerium nitrate and neodymium chloride.
3. The method for preparing a porous drag-reducing coating according to claim 1, characterized in that: The mass fractions of natural polymer, cellulose nanocrystal and two-dimensional nanomaterial in the mixed solution are 0.5-10wt%, 0.1-10wt% and 0.01-5wt% respectively; The mass fraction of the metal salt in the metal salt solution is 0.01-10wt%.
4. The method for preparing a porous drag-reducing coating according to claim 1, characterized in that: The silane coupling agent is at least one of vinyl triethoxysilane, methacryloxypropyl trimethoxysilane and γ-mercaptopropyl triethoxysilane; The inorganic precursor is at least one of tetraethyl orthosilicate and tetrabutyl titanate; The inorganic salt is at least one of sodium chloride, magnesium chloride and sodium sulfate; The adhesive polymer is at least one of polyurethane, amino silicone resin, and fluorocarbon resin; The organic solvent is at least one of methanol and ethanol.
5. The method for preparing a porous drag-reducing coating according to claim 1, characterized in that: The mass fractions of the silane coupling agent, the inorganic precursor and the inorganic salt adhesive polymer in the organic-inorganic mixed liquid are 5-10wt%, 0.5-15wt%, 0.5-10wt% and 0.5-5wt% respectively.
6. The method for preparing a porous drag-reducing coating according to claim 1, characterized in that: The hot pressing temperature is 60-120° C., and the hot pressing time is 0.5-24 hours.
7. The method for preparing a porous drag-reducing coating according to claim 1, characterized in that: The treatment of the metal ion coordinated cross-linked coating by directional freeze casting technology refers to: freezing for 0.5-24 hours in a -60°C to -4°C environment, and then freeze drying for 6-72 hours.
8. The method for preparing a porous drag-reducing coating according to claim 1, characterized in that: The organic-inorganic mixed solution also includes an additive with a mass fraction of 0.5-10wt%, and the additive is at least one of montmorillonite, diatomaceous earth and halloysite.
9. The method for preparing a porous drag-reducing coating according to claim 1, characterized in that: The reaction temperature for obtaining the organic-inorganic mixed solution is 5-65°C.
10. A porous drag-reducing coating, characterized in that: The porous drag-reducing coating is prepared by any preparation method according to claims 1-9.
Citation Information
Patent Citations
Super-hydrophilic anti-drag coating with porous structure and preparation method of super-hydrophilic anti-drag coating
CN116554715A
Antifouling anti-drag super-hydrophobic coating as well as preparation method and application thereof
CN117567917A
Multi-layer composite material with multi-antifouling synergistic flexible reinforced drag reduction characteristic as well as preparation method and application of multi-layer composite material
CN118558568A
Cited By
Coating composition for nano coating capable of reducing wind resistance and preparation method of coating composition
CN122255792A